THE PREDICTION OF TOLAKI LANGUAGE EXTINCTION AT PUNGGALUKU VILLAGE, LAEYA SUB DISTRICT, SOUTH KONAWE REGENCY - Nurhidayati, Hesti; Hanna, Hanna; Suhartini, Lelly (Universitas Halu Oleo, 2020)
This research discussed the language extinction in Tolaki language for Tolakinese who lived in Punggaluku village. Language contact that has occurred at multilingual society in Punggaluku became an interesting phenomenon to be learnt because it had close relationship with the use of ethnic language of the residents in this village. This study focused on the endangered level of Tolaki language extinction and predicted the Tolaki language extinction at Punggaluku Village, Laeya Sub district. The main data of the research were taken in Punggaluku Village, Laeya Sub district, South Konawe Regency. Observation and interview were used by the researcher in collecting the data from informants in this area. The result of this research showed that Tolaki language was potentially threatened as a severely endangered language. It was indicated from the parents were not transmitted Tolaki language to their children and the low frequency in using Tolaki language among old generation. It caused the young generation could not speak Tolaki language and final effect of this phenomenon was language extinction. Futhermore, the researcher predicted 30 years ahead, Tolaki language will be extincted in Punggaluku village, Laeya Sub District, South Konawe Regency.